Single-Dose Pharmacokinetics and Pharmacodynamics of IPX203 in Patients With Advanced Parkinson Disease: A Comparison With Immediate-Release Carbidopa-Levodopa and With Extended-Release Carbidopa-Levodopa Capsules - Modi, Nishit B. (Clin Neuropharmacol, 2019)
OBJECTIVE: IPX203 is an investigational oral extended-release capsule formulation of carbidopa-levodopa (CD-LD). The aim of this study was to characterize the single-dose pharmacodynamics, pharmacokinetics, and safety of IPX203 in subjects with advanced Parkinson disease compared with immediate-release (IR) CD-LD and extended-release CD-LD (Rytary). METHODS: This was a randomized, open-label, rater-blinded, multicenter, single-dose crossover study. Blinded clinicians assessed subject's motor state and Movement Disorders Society Unified Parkinson's Disease Rating Scale (MDS-UPDRS) part III scores for up to 10 hours postdose. Duration of effect was determined using improvement thresholds in the MDS-UPDRS part III. RESULTS: Levodopa concentrations increased rapidly and similarly across all 3 treatments and were sustained for a longer duration after IPX203 dosing. All treatments exhibited a rapid onset of pharmacodynamic effect, whereas IPX203 had a significantly longer duration of effect based on MDS-UPDRS part III scores compared with IR CD-LD (P < 0.0001) and Rytary (P ≤ 0.0290). IPX203 had a 2.7-hour advantage over IR CD-LD (P < 0.0001) and a 0.9-hour advantage over Rytary in “off” time (P = 0.023) and in “good on” time (2.6 hours more than IR CD-LD, P < 0.0001; 0.9 hours more than Rytary, P = 0.0259) as measured by the Investigator Assessment of Subject's Motor State. Subjects were 77% more likely to require rescue following IR CD-LD treatment compared with IPX203 (hazard ratio, 0.23; P < 0.0001). More subjects reported treatment-emergent adverse effects during IR CD-LD (28.0%) and IPX203 (19.2%) than during Rytary (8.0%) treatment. CONCLUSIONS: Compared with Rytary and IR CD-LD, IPX203 had a longer pharmacodynamic effect consistent with LD pharmacokinetics for the 3 treatments. The safety and tolerability of IPX203 were similar to those of IR CD-LD and Rytary.